Early-Onset Chronic Inflammatory Disease Associated with Maternal Microchimerism. (9th August 2012) - Ishikawa, Tomoaki; Sakurai, Yoshihiko; Takeda, Tomohiro; Suzuki, Hiroshi
Abstract : Maternal microchimerism (mMc) refers to the presence of a small population of cells originating from the mother. Whether mMc leads to autoimmune responses in children remains controversial. We describe here an 11-year-old boy with persistent fever and elevated levels of C-reactive protein from infancy onward. During infancy, the patient presented with high fever, skin rashes, and hepatic dysfunction. Careful examination including a liver biopsy failed to reveal the cause. At 4 years old, petechiae developed associated with thrombocytopenia and positive anti-dsDNA autoantibodies. Steroid pulse therapy was effective, but the effect of low-dose prednisone was insufficient. At age 9, an extensive differential diagnosis was considered especially for infantile onset autoinflammatory disorders but failed to make a definitive diagnosis. On admission, the patient exhibited short stature, hepatosplenomegaly, generalized superficial lymphadenopathy, and rashes. Laboratory findings revealed anemia, elevated levels of inflammation markers, and hypergammaglobulinemia. Serum complement levels were normal. Serum levels of IL-6 and B-cell activating factor were elevated. Viral infections were not identified. Although HLA typing revealed no noninherited maternal antigens in lymphocytes, female cells were demonstrated in the patient's skin and lymph nodes, suggesting that maternal microchimerism might be involved in the pathogenesis of fever without source in infants.